Ochratoxin A in Rice Marketed in Lebanon - Charara, Abeer (2021)
Rice is one of the world's most widely consumed foods. A. Circumdati, A. Nigri, P. verrucosum, and P. nordicumcan contaminate rice in subtropical and tropical hot and humid climates and secrete mycotoxins, like the toxic and carcinogenic ochratoxin A (OTA). Our research aims to investigate the amounts of OTA in packaged rice sold in Lebanon and the exposure to this toxin from rice consumption. A total of 105 packed white, parboiled, and brown rice bags were collected, with 86 of them coming from 43 different brands. OTA was measured using Enzyme-Linked Immunosorbent Assay (ELISA) technique. In parallel, two hundred participants completed a detailed food frequency questionnaire to determine rice consumption patterns and, as a result, OTA exposure levels from rice intake in Lebanon. OTA was detected in 105 out of 105 (100%) of the rice samples. The average concentration ± standard deviation of OTA was 0.42 ± 0.09 μg/kg. Contamination ranged between 0.02 and 4.98 μg/kg. Moisture content in all rice samples was below the limit (14%). Only 2 rice samples had an OTA level close to the EU limit (5 μg/kg) and were considered as outliers. A significant difference was found between both collections for the same brands (p<0.001). Rice type, packing season, packing country, country of origin, presence of a food safety management certification, grain size, and time between packing and purchasing had no significant effect on OTA in rice. Exposure to OTA from rice consumption in Lebanon was calculated as 0.02-4.89 ng/kg body weight/day with an average of 0.41 ng/kg body weight/day. Future studies should assess OTA in unpacked rice, and routine monitoring must be carried out to consider emerging brands in the Lebanese market.